Influence of knowledge, advertising, and price on Gen Z’s eco-friendly purchase decisions for The Body Shop - Dina Puspita Sari; Tri Nur Wahyudi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aims to analyze the influence of environmental knowledge, advertising, and price on purchasing decisions for environmentally friendly products among Generation Z, with a case study on consumers of The Body Shop products. The research employed a quantitative approach by distributing questionnaires to 122 respondents aged 18–27 who had purchased The Body Shop products. Data were analyzed using the Partial Least Squares (SmartPLS) method. The results show that environmental knowledge, advertising, and price have a positive and significant effect on purchasing decisions, with an R-square value of 0.692, indicating that the three variables explain 69.2% of the variance in purchasing decisions. These findings suggest that higher environmental knowledge, positive perceptions of advertising, and appropriate price evaluations increase Generation Z’s tendency to purchase environmentally friendly products. This research provides implications for companies to design marketing strategies focusing on environmental education, creative communication, and competitive pricing.